Low pH resistant lactic acid bacteria from cow rumen waste - Ahimsa Kandi Sariri; Kustantinah Kustantinah; Zaenal Bachruddin; Chusnul Hanim (Indonesian Journal of Biotechnology, 2025)
This study aims to obtain a new strain of lactic acid bacteria (LAB) with the ability to survive at low pH, resulting from isolation, selection, and identification from rumen waste. The research included four stages: isolation of bacteria from rumen waste, selection, and identification. The selection procedure involved growth of LAB in a low pH medium. Molecular identification procedure was conducted using the 16S rRNA gene sequence amplification method with universal primers 27F (AGAGTTTGATCCTGGCT CAG) and 1429R (TAGGGTTACCTTGTTACGACTT). The results of the isolation and identification were analyzed descriptively, revealing that five petri dishes (5a, 10a, 10b, 16a, and 18b) contained lactic acid bacteria which produced clear zones. Among these, isolate 18b was the only LAB strain that survived in a pH 3.5 medium. The results of the molecular identification using the 16s rRNA gene showed that isolate 18b belonged to Limosilactobacillus fermentum.